ANALISIS PENYAJIAN LAPORAN KEUANGAN PEMERINTAHAAN KABUPATEN TULUNGAGUNG - Rachmat Sandy Ramadhan; Akie Rusaktiva Rustam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the presentation of financial statements has been fully implemented Tulungagung follow SAP PP No. 71 Year 2010 annex II. This research is descriptive qualitative. The data in this study were obtained by means of field studies is through interview, observation, and documentation. The process of data analysis using qualitative methods, which include analysis of financial statement presentation system that currently run vBulletin district government as outlined in the accounting policies as compared with SAP No.. 71 (Annex II). The results of this study showed that based on its Financial Statements components BPKAD Tulungagung have followed SAP No.. 71 of 2010 (Appendix II). Yet the budget realization report, the presentation of the financing is still not converted post by SAP and still follow the classification or labeling by post or by post Permendagri financing district government budget in vBulletin. Keywords: Presentation of Financial Statements, SAP PP No 71, Region Tulungagung.